Impact of congenital heart disease on outcomes among pediatric patients hospitalized for COVID-19 infection - Laxmi V Ghimire; Fu-Sheng Chou; Othman A. Aljohani; Anita J. Moon-Grady (BMC, 2023)
Abstract Background COVID-19 infection is generally regarded as an acute self-limiting illness in children, but it can cause significant morbidity and mortality in both healthy and high-risk children. There are limited data on the outcomes of children with congenital heart disease (CHD) and COVID-19. This study aimed to examine the risks of mortality, in-hospital cardiovascular and non-cardiovascular complications in this patient population. Methods We analyzed data from hospitalized pediatric patients from 2020 using the nationally representative National Inpatient Sample (NIS). Children hospitalized for COVID-19 were included, and weighted data were used to compare in-hospital mortality and morbidities between children with and without CHD. Results Out of 36,690 children admitted with a diagnosis of COVID-19 infection(ICD-10 code:U07.1 and B97.29) during calendar year 2020, 1240 (3.4%) had CHD. The risk of mortality in children with CHD was not significantly higher than those without CHD(1.2% vs. 0.8%, p = 0.50), with adjusted OR (aOR) of 1.7 (95% CI: 0.6-5.3). Tachyarrhythmias and heart block were more likely in CHD children with an aOR of 4.2 (95% CI: 1.8-9.9) and aOR of 5.0 (95% CI: 2.4-10.8), respectively. Similarly, respiratory failure [aOR = 2.0 (1.5-2.8)], respiratory failure requiring non-invasive mechanical ventilation [aOR = 2.7 (1.4-5.2)] and invasive mechanical ventilation [aOR = 2.6 (1.6-4.0)], and acute kidney injury [aOR = 3.4 (2.2-5.4)] were all significantly higher among patients with CHD. Median length of hospital stay in children with CHD was longer than those without CHD [5 days (IQR: 2-11) vs. 3 days (IQR: 2-5), p = < 0.001]. Conclusions Children with CHD hospitalized with COVID-19 infection were at increased risk of serious cardiovascular and non-cardiovascular adverse clinical outcomes. They also had increased length of hospital stay and utilization of healthcare resources.